Leaf age-related differences in apoplastic NH(4)(+) concentration, pH and the NH(3) compensation point for a wild perennial - Hill, P W (Journal of experimental botany, 2002)
Extracts of the foliar apoplast of leaves of different ages of Luzula sylvatica (Huds.) Gaud. were prepared by vacuum infiltration and centrifugation. Measurements of pH and concentration were performed on extracts. From these bioassay measurements the relative magnitude of NH(3) compensation points for leaves of different ages were inferred. Young leaves were found to have much higher apoplast pH than old leaves, leading to the calculation of 4-10-fold higher NH(3) compensation points. Such age-related differences in the NH(3) compensation point are considerably larger than those previously reported. Apoplast pH and concentration were found to increase during leaf expansion before declining prior to senescence. Bulk foliar tissue pH, and total N concentrations were also found to be generally higher in young leaves than in old leaves. Where a significant correlation was found, total foliar N, bulk tissue foliar and the calculated NH(3) compensation point were all found to increase with N supplied to roots, whilst apoplast and bulk tissue H(+) concentrations were found to decline. The potential of bulk foliar tissue measurements to act as simple predictors of the NH(3) compensation point is discussed